Java-Powered AI: Implementing Intelligent Systems with Code - Vyas, Bhuman (Journal of Science & Technology, 2023)
The fusion of Artificial Intelligence (AI) and Java programming offers a powerful synergy, enabling developers to create intelligent systems and applications with efficiency, robustness, and scalability. This paper explores the amalgamation of Java’s versatility and AI’s cognitive capabilities, presenting various techniques, libraries, and methodologies that leverage Java’s strengths in building AI-driven solutions. The paper commences with an overview of AI concepts and the landscape of Java’s role in AI development. It delves into fundamental AI algorithms, such as machine learning, natural language processing (NLP), computer vision, and reinforcement learning, elucidating their implementation in Java through frameworks like Deeplearning, Weka, and Apache OpenNLP. Furthermore, it discusses the utilization of Java in crafting intelligent agents and exploring techniques for creating autonomous decision-making systems, expert systems, and heuristic-driven algorithms. It highlights the integration of Java with AI-enabled tools, emphasizing the importance of data preprocessing, feature engineering, and model deployment. Moreover, the paper examines the challenges and opportunities in Java-based AI development, addressing concerns related to performance optimization, compatibility with diverse data sources, and the interoperability of AI modules. Finally, the paper concludes with a glimpse into the future of Java-powered AI, envisioning advancements in Java libraries, frameworks, and methodologies that will foster the creation of more sophisticated, intelligent systems.